Analisis Validitas e-Book Berbasis Higher Order Thinking Skills Pada Materi Gerak Melingkar - Millah, Nayla 'Izzata; Kholiq, Abd. (IPF: Inovasi Pendidikan Fisika, 2023)
This study aims to describe the feasibility of a HOTS-based e-book on circular motion material in terms of its validity. This research is development research with the ADDIE research design. In this study, there were three stages that were carried out consisting of the analysis stage, namely knowing the needs of students and teachers for learning media, design, namely the preparation of designs and indicators of high-level thinking skills to be used in HOTS-based e-books, and development, namely the validation of HOTS-based e-Books conducted by three validators who are expert lecturers. The validity of e-books is viewed from four aspects, namely aspects of language, media, materials, and HOTS indicators. The results showed that the percentage of validity in the language aspect was 97.92%, in the media aspect it was 97.73%, in the material aspect it was 98.81%, and in the HOTS indicator aspect it was 97.22%. Based on these results, the validity of the e-book gets an average percentage of 97.92% with a very valid category. So, it can be concluded that HOTS-based e-Books are declared valid to be used as physics learning media to improve students' high-level thinking skills in circular motion material. Keywords: e-Book, Higher Order Thinking Skills, Circular Motion